PANDANGAN PEMIMPIN GEREJA TENTANG PENGATURAN ORGANISASI GEREJA DI PROVINSI PAPUA (Harmoni, 2015)
This study discusses church leader viewpoints on church organization management in Papua. The study uses qualitative approach that aims to describe the religious leaders viewpoints related to services, counseling, and organization management or denomination of church and Christian board by ministry religious affair in Papua. The study describes contributions of Christian leadersΓÇÖ visionary thought in Papua to establish religious harmony and peacefulness that there are some new denominations to get legalization from the government after determination of Act No.17, 2013 about community organization. The result of study can be concluded that church leaders agree that organization management conducted by ministry religious affair in Papua is good and they have same perception on making a good relationship to make peace in Papua and uphold ΓÇ£satu tungku tiga batuΓÇ¥ motto to build strong relationship between adherents and religious leaders. Generally, the relationship between Christians and society around the church as well between church and ministry religious affair is good.
Keywords: Church denomination; viewpoints; organization; Denominasi Gereja; Pandangan; Organisasi